Racial discrimination and socioemotional and sleep problems in a cross-sectional survey of Australian school students. Issue 11 (28th July 2020) - Priest, Naomi; Chong, Shiau; Truong, Mandy; Alam, Oishee; Dunn, Kevin; O'Connor, Meredith; Paradies, Yin; Ward, Andrew; Kavanagh, Anne
Abstract : Objective: To determine the prevalence of direct and vicarious racial discrimination experiences from peer, school and societal sources, and examine associations between these experiences and socioemotional and sleep outcomes. Methods: Data were analysed from a population representative cross-sectional study of n=4664 school students in years 5–9 (10–15 years of age) in Australia. Students reported direct experiences of racial discrimination from peers, school and societal sources; vicarious discrimination was measured according to the frequency of witnessing other students experiences of racial discrimination. Students self-reported on the Strengths and Difficulties Questionnaire, with the total difficulties, conduct, emotional and prosocial behaviour subscales examined. Sleep problems included duration, latency, and disruption. Results: 41.56% (95% CI 36.18 to 47.15) of students reported experiences of direct racial discrimination; Indigenous and ethnic minority students reported the highest levels. 70.15% (95% CI 63.83 to 75.78) of students reported vicarious racial discrimination. Direct and vicarious experiences of racial discrimination were associated with socioemotional adjustment (eg, for total difficulties, total direct racism: beta=3.77, 95% CI 3.11 to 4.44; vicarious racism: beta=2.51, 95% CI 2.00 to 3.03). Strong evidence was also found for an effect of direct and vicarious discrimination on sleep (eg, for sleep duration, total direct: beta=−21.04, 95% CI −37.67 to −4.40; vicarious: beta=−9.82, 95% CI −13.78 to −5.86). Conclusions: Experiences of direct and vicarious racial discrimination are common for students from Indigenous and ethnic minority backgrounds, and are associated with socioemotional and sleep problems in adolescence. Racism and racial discrimination are critically important to tackle as social determinants of health for children and adolescents.